PERANAN PIK REMAJA DALAM MENYONGSONG BONUS DEMOGRAFI DI WILAYAH PERKOTAAN - Maskur Maskur; Tahir Kasnawi; Mursalim Mursalim (Jurnal Inovasi Penelitian, 2021)
Population problems in Indonesia have entered a fairly serious stage and if not overcome immediately will cause a disaster, especially for adolescent age groups where their problems are so complex. The purpose of this research is to know the role of youth information and counseling center in addressing demographic bonuses in urban areas. This research was conducted with qualitative approach, as field research to understand the phenomenon about role, behavior, perception and action natural by adolescent. Given the age group of adolescents greatly determines the direction of future development in achieving the desired demographic bonus. With the provision of adolescent knowledge gained through the active Youth Information and Counseling Center has attitudes, future behavior and perspective have aspirations for continuing education, finding employment, planning family life and become a member of society and practice healthy life. Seen the board of the Center for Information and Counseling Teenagers do education and counseling related dangers Triad Reproductive Health Teenagers outside and inside the school, Teenagers are also actively developing self potential and continue to hone as an added value, youth Information Center And Counseling can be a role model in school as models and examples that have attitudes, healthy behaviors, they also get a mandate from teachers Counseling Guidance to counsel to friends who have problems. They actively participate in educational exhibitions, wall magazine discussions and educational motivation to peers and have annual career preparation training activities that must be followed by the board. the Youth Information and Counselors Information Center can be a source of information for peers in overcoming the problems that appear to them.